Analysis of Public Perceptions of the Government's Role in Increasing Community Participation: A Quantitative Approach - Ragoan Alhamid; Charis Christiani; Sumarmo Sumarmo (International Journal of Social Science and Humanity, 2026)
Government and government transparency on community participation, with government accountability as an intervening variable. The study used a quantitative approach based on Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were obtained through questionnaires distributed to the community of Maladum Mes District, Sorong City. The results show that government transparency and public perception of the government's role have a positive and significant effect on government accountability. In addition, government transparency, public perception, and government accountability have a positive and significant effect on community participation. The mediation test results show that government accountability partially mediates the effects of government transparency and public perception of the government's role on community participation. These findings confirm that increasing community participation depends not only on information disclosure and positive perceptions, but also on the extent to which the government is accountable to the public for its performance. This study offers theoretical implications for strengthening the concept of good governance and practical implications for local governments in designing participatory policies.